X-men: the animated series - feared and hated ebook - Macchio, Ralph (X-Men Adventures (1992),, 2024)
Collects Collecting X-Men Adventures (1992) #1-8. Exploding from your TV screen! The iconic X-MEN: THE ANIMATED SERIES thrilled fans in the 1990s and defined the X-Men for an entire generation. And their small-screen adventures, inspired by the X-Men's classic storylines, were adapted into comic-book form as well! Cyclops, Jean Grey, Storm, Wolverine, Rogue, Gambit, Beast, Jubilee and Morph are Professor X's Uncanny X-Men - ready to battle threats including Sabretooth, the Juggernaut and Magneto, Master of Magnetism! But when the mutant-hunting robotic Sentinels attack, one of the team will pay the ultimate price! Plus: The X-Men battle the misunderstood Morlocks - and from the far future comes the freedom-fighting soldier called Cable!